2017
DOI: 10.1242/jeb.158543
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic costs imposed by hydrostatic pressure constrain bathymetric range in the lithodid crab Lithodes maja

Abstract: The changing climate is shifting the distributions of marine species, yet the potential for shifts in depth distributions is virtually unexplored. Hydrostatic pressure is proposed to contribute to a physiological bottleneck constraining depth range extension in shallow-water taxa. However, bathymetric limitation by hydrostatic pressure remains undemonstrated, and the mechanism limiting hyperbaric tolerance remains hypothetical. Here, we assess the effects of hydrostatic pressure in the lithodid crab (bathymetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…Wittmann et al, 2010;Brown, 2015) and is reported in colder waters (0 • C) than Southern Ocean lithodids (0.2 • C) (cf. Hall and Thatje, 2011;Brown et al, 2017). Consistent with this hypothesis, heart rate is greater in L. maja than in the sub-Antarctic lithodid Paralomis granulosa at 0.1 MPa and 6 • C; respectively ∼28 bpm and ∼21 bpm at rest (Wittmann et al, 2012).…”
supporting
confidence: 54%
See 4 more Smart Citations
“…Wittmann et al, 2010;Brown, 2015) and is reported in colder waters (0 • C) than Southern Ocean lithodids (0.2 • C) (cf. Hall and Thatje, 2011;Brown et al, 2017). Consistent with this hypothesis, heart rate is greater in L. maja than in the sub-Antarctic lithodid Paralomis granulosa at 0.1 MPa and 6 • C; respectively ∼28 bpm and ∼21 bpm at rest (Wittmann et al, 2012).…”
supporting
confidence: 54%
“…Hyperbaric tolerance in L. maja is also limited by hyperbaric effects on heart rate (Brown et al, 2017). Decreasing heart rate observed in L. maja in response to increasing hydrostatic pressure is similar to the decrease in heart rate observed in P. granulosa in response to decreasing temperature, suggesting that [Mg 2+ ] regulation may also critically influence hyperbaric performance.…”
mentioning
confidence: 55%
See 3 more Smart Citations